Host-guest interactions in pure-silica and aluminosilicate sodalites containing ethylene glycol as a guest molecule - Hong, SB; Camblor, MA; Davis, ME (AMER CHEMICAL SOC, 1997)
Four sodalite materials with Si/Al ratios of infinity, 23.0, 11.0, and 5.7 are synthesized from essentially nonaqueous media in which ethylene glycol is acting both as a solvent and as a structure-directing agent. Elemental and thermal analyses, X-ray powder diffraction, multinuclear MAS NMR, and vibrational spectroscopies are employed to extensively investigate the host-guest interactions in as-synthesized materials. It is found that the hydrogen-bonding feature of the ethylene glycol molecules encapsulated within the P-cages of sodalites is strongly affected by the Al content in the framework. The overall results of this study lead us to conclude that the molecular conformation of ethylene glycol in the pure-silica beta-cage may be tGg' stabilized only by one intramolecular hydrogen bond, while that of the guest molecule in the beta-cage with a Si/Al ratio of 5 is gGg' stabilized by one strong hydrogen bond to ; the framework in addition to one intramolecular hydrogen bond.
Keywords: SI-29 CHEMICAL-SHIFTS; NONAQUEOUS SYNTHESIS; CRYSTAL-STRUCTURES; ZEOLITES; RAMAN; SPECTRA; DYNAMICS; SYSTEMS; SIEVES; AL-27